Synthesis new substances of norbornene`s series toward photochemical energy storage - S. V. Leont`eva; V. R. Flid (Тонкие химические технологии, 2007)
Modification of norbornadien (NBD) for using as solar energy storage was attempted. Synthesed adducts was investigated in the reaction of catalytic allylation by Pd3(OAc)6 – PPh3 and Ni(C3H5)2 – P(i-C3H7O)3 complexes and reaction parametres were optimized. Supramolecular substances, combinated NBD and 4-oxoretinal or 5,6-dioxo-5,6-sekoretinal, were suggested toward photochemical energy storage and optical memory systems by means of the photochromic valence isomerization of the NBD – quadricyclane system.